Why do peers influence college major selection? - Insler, Michael A.; Rahman, Ahmed S.; Smith, Katherine A. (Economic Inquiry, 2025)
Why do peers influence people's choices? Is it for information (social learning) or for socializing (social utility)? Exploiting unique data and natural experiments from the United States Naval Academy (USNA), we analyze data on major selections of USNA students. We find peers influence students into selecting different academic paths than they would have chosen independently. Through random reassignments, "shot‐guns", of students into new peer groups along with random assignments into courses, we explore the reasons why herding occurs. Evidence suggests that social learning, as opposed to social utility, is an important driver for herding behavior.